Preparing Future Leaders for Immediate Response to Emergencies through Mindfulness Education - Han, Hongmei; Preston , Joanne C (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
Leadership preparedness is essential for immediate response to emergencies to reduce losses and save lives. This study adopted a mixed-method approach to study the effects of a customized intervention program, an elective course entitled Mindful Leadership, on college students’ leadership preparedness for immediate emergency responses. A pre-post study design was implemented among the targeted group of 41 undergraduates. Mixed results were produced after sixteen weeks of intervention. The quantitative data presented significant pre-post difference in self-awareness, but no significant differences in other sub-variables of leadership preparedness. However, the qualitative data were more encouraging and provided deeper insights, indicating that mindfulness education was beneficial to the development of the participants’ leadership preparedness. Hence, this study evidenced that a mixed-method approach enables a better understanding of the research questions, especially when the participants are not mature enough for a survey alone to detect their changes after an intervention.